Is The Legend of Zelda: Breath of the Wild a Modern Day Fairy Tale? - Reed, Cody Nikolas (URJ-UCCS: Undergraduate Research Journal at UCCS, 2021)
Are fairy tales still receiving cultural significance in modern-day mediums – such as within the gaming industry? This essay aims to answer that question by analyzing the relationship The Legend of Zelda: Breath of the Wild has with Masculinity and Queer Theory, and how this directly parallels the lesser-known fairy tale of Iron Hans, written by the Jacob and Wilhelm Grimm. By analyzing other significant scholars of fairy tale literature, this paper shows that the conversation of modern-day fairy tales can be applied to new mediums and shed new light into areas unexplored.